President's Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2020)
After working diligently with our Board of Directors I am excited to announce that our new three- year Strategic Plan will be ready for launch this Fall and it will be shared with members. The new plan focuses on a revitalization of ORNAC and bringing additional value to our Members.